ANALYSIS OF COMMON SIZE PT. SEMEN INDONESIA (PERSERO) Tbk - Puji Suryani, Suci; Zysman, John; Akhyar, Chairil; Sinta, Irada; Nur Ilham, Rico (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The Indonesian economy has experienced growth or decline due to several things, one of which is by State-Owned Enterprises. Financial statements can provide useful information as a tool to understand the financial performance of a company. The purpose of this study is to analyze the financial performance of PT Semen Indonesia (Persero) Tbk which is listed on the Indonesia Stock Exchange from 2019 to 2021 in terms of financial statements with total assets or liabilities presented in the balance sheet and income statement using common size analysis. The results of quantitative descriptive research using processed secondary data indicate that the company is still relatively healthy and the company's financial performance on the balance sheet is in a fairly good condition. However, the financial performance on the income statement shows that the marketing strategy is less effective in terms of increasing revenue and has not been able to provide long-term profitability.